2013
DOI: 10.1371/journal.pbio.1001492
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Mechanism of Substrate Engagement and Immunosuppressant Inhibition of Calcineurin

Abstract: Structural analyses show that a viral protein and immunosuppressant drugs inhibit the phosphatase calcineurin by preventing substrate binding, and provide a model of a phosphatase engaged with its substrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
197
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(210 citation statements)
references
References 56 publications
11
197
1
1
Order By: Relevance
“…Recently, Grigoriu et al [24] reported the first high-resolution structure of CN α bound to a physiological binding partner, the protein inhibitor A238L from African swine fever virus. The structure of the CN-A238L complex reveals that the interface between these two proteins consists of two discontinuous contact regions.…”
Section: The Cna-cnb Interface Is a General Recognition Site For Aismentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Grigoriu et al [24] reported the first high-resolution structure of CN α bound to a physiological binding partner, the protein inhibitor A238L from African swine fever virus. The structure of the CN-A238L complex reveals that the interface between these two proteins consists of two discontinuous contact regions.…”
Section: The Cna-cnb Interface Is a General Recognition Site For Aismentioning
confidence: 99%
“…Although the structure of CN bound to a bona fide substrate has yet to be determined, the structure of the CN-A238L complex provides the structural basis for the computational model of CN with a phosphosubstrate bound to its active site [24]. The pRII peptide (a 19-amino-acid phosphopeptide) contains a typical LxVP motif that is required for its recognition and efficient dephosphorylation by CN.…”
Section: The Cna-cnb Interface Is a General Recognition Site For Aismentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, LxVP peptides bind to a hydrophobic groove formed by the CN A and B subunits that is accessible only after Ca 2+ /calmodulin binding activates the enzyme and releases an autoinhibitory peptide (AIS) from this site 10 . Engagement of the LxVP binding site is required for dephosphorylation and is thought to orient the phosphorylated residue toward the catalytic center 11 . In combination with an immunophilin, FK506 and CysA binds to this LxVP-binding site, thus inhibiting CN by blocking its interaction with NFAT and other substrates 8,11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…Engagement of the LxVP binding site is required for dephosphorylation and is thought to orient the phosphorylated residue toward the catalytic center 11 . In combination with an immunophilin, FK506 and CysA binds to this LxVP-binding site, thus inhibiting CN by blocking its interaction with NFAT and other substrates 8,11,12 . Unfortunately, inhibition of the ubiquitous CN in non-immune tissues often leads to kidney failure, diabetes, pain, or seizures 13 , presumably due to interaction with as-yet-unidentified substrates.…”
Section: Introductionmentioning
confidence: 99%